2016
DOI: 10.1007/s00428-016-1970-5
|View full text |Cite
|
Sign up to set email alerts
|

MUC1, MUC2, MUC5AC, and MUC6 in colorectal cancer: expression profiles and clinical significance

Abstract: Mucin glycoprotein expression can be altered during the carcinogenic process. The impact on the prognosis of patients with colorectal cancer (CRC) is controversial. We analyzed tumors from 381 patients for MUC1, MUC2, MUC5AC, and MUC6 expression by immunohistochemical staining, using tissue microarrays. Progression-free and cancer-specific survival were determined using the Kaplan-Meier method. Expression of intestinal mucin MUC2 was lost in 85 (23 %) CRCs, and patients with MUC6-negative tumors showed shorter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
97
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(104 citation statements)
references
References 32 publications
7
97
0
Order By: Relevance
“…Tumour antigens survivin and MUC1 are both reported to be upregulated and associated with the recurrence, metastasis and drug resistance in many cancers . In our previous research, survivin and MUC1 showed a better antitumour effect when combined in a vaccine than when given separately in a murine melanoma model .…”
Section: Introductionmentioning
confidence: 81%
“…Tumour antigens survivin and MUC1 are both reported to be upregulated and associated with the recurrence, metastasis and drug resistance in many cancers . In our previous research, survivin and MUC1 showed a better antitumour effect when combined in a vaccine than when given separately in a murine melanoma model .…”
Section: Introductionmentioning
confidence: 81%
“…Each adenocarcinoma had intestinal‐type morphology and expressed CDX2, and neither showed the ductal appearance of anal gland carcinoma or the predominantly mucinous phenotype of fistula‐associated adenocarcinoma. One of the adenocarcinomas (case 2) did not show MUC2 immunopositivity, but this absence does not exclude an intestinal phenotype, especially as approximately a quarter of colorectal carcinomas do not express this glycoprotein . The tumours arose in the peri‐anal region and/or anal verge but were clearly distal from the dentate line and the columnar cuff.…”
Section: Discussionmentioning
confidence: 96%
“…One of the adenocarcinomas (case 2) did not show MUC2 immunopositivity, but this absence does not exclude an intestinal phenotype, especially as approximately a quarter of colorectal carcinomas do not express this glycoprotein. 6 The tumours arose in the peri-anal region and/ or anal verge but were clearly distal from the dentate line and the columnar cuff. Both cases showed carcinoma beneath squamous epithelium, with no overlying columnar mucosa or adenoma.…”
Section: Discussionmentioning
confidence: 99%
“…4e,i). Organoid cells express AGR2 and other mucin family genes like MUC5AC and MUC5B, which are not expressed by the patients' cells but are expressed in intestinal cells and gastrointestinal cancers [42][43][44][45] (Extended Data Fig. 8b).…”
Section: Our Comparison Between the Patients' Cells And Organoid Cellmentioning
confidence: 99%